Case Report: Neonatal Complex Congenital Heart Disease With Anomalous Origin of the Left Coronary Artery From the Right Pulmonary Artery: Analysis of Missed Diagnosis and Improvement Procedures - Bing, Zhen; Liu, Leilei; Chen, Rui; Cao, Qian; Ge, Wen (Frontiers in Pediatrics, 2022)
The anomalous origin of the left coronary artery from the right pulmonary artery is a rare type of anomalous origin of the left coronary artery from the pulmonary artery. It is even rarer when combined with complex congenital heart diseases requiring surgical intervention in the neonatal period. Because it has no clinical manifestations in the neonatal period, it is easier to miss diagnosis when combined with complex congenital heart disease. To avoid a missed diagnosis of anomalous origin of the left coronary artery from the right pulmonary artery, preoperative echocardiography should routinely explore the orifice of the coronary artery. However, the preoperative examination can lead to missed diagnosis due to the influence of the examiner's experience, equipment, and other factors. After thoracotomy, exploring the orifice position of the left and right coronary arteries can avoid the missed diagnosis of the abnormal origin of coronary arteries. Exploration of the coronary artery is mainly recommended for children with complex congenital heart disease in the neonatal period and children with congenital heart disease combined with unexplained cardiac insufficiency and abnormal mitral valve development.